Empowering challenges of missional ecclesiology and leadership at the grassroots level - Johannes J. Knoetze (Verbum et Ecclesia, 2025)
This article examines the work of Nelus Niemandt within both the academy and the church, with a particular focus on his understanding of missionality as shaped by his perspectives on spirituality, ecclesiology and leadership. It also explores key elements of discernment and service leadership. To have a better understanding of service leadership, attention is given to the diak- word-group in the New Testament. While some critiques suggest that Niemandt’s writings on ecclesiology and leadership lack practical application, this article highlights the tangible impact of his work at the grassroots level. Specifically, it considers outcomes within the Dutch Reformed Church, such as the adoption of a missional ecclesiology and the development of new ministerial pathways to equip and empower missional leaders. This article concludes with two examples from the development of the additional ministerial tracks. Two members who did the studies witness of how a missional ecclessiological understanding in the Dutch Reformed Church has made it possible for them to live their calling. It is also clear from these witnesses that in many congregations we still have a long walk in obedience and discernment to become more missional than institutional.